Rational Control of Topological Defects in Porous Carbon for High‐Efficiency Carbon Dioxide Conversion. Issue 7 (24th February 2021) - Jiang, Pengfei; Jiang, Kaiyue; Tranca, Diana; Zhu, Jinhui; Qiu, Feng; Ke, Changchun; Lu, Chenbao; Kymakis, Emmanuel; Zhuang, Xiaodong
Abstract: Nitrogen‐doped porous carbons have been extensively studied for electrocatalysis, including the electrocatalytic CO2 reduction reaction. Most relevant studies have focused on nitrogen sites in porous carbons, however, the intrinsic topological defects of porous carbons have been usually ignored because of difficulties in controllable preparation, structural identification, and determining structure–property correlations. In this study, topological defect‐enriched porous carbons are fabricated through pyridinic‐N volatilization at a high temperature by using nitrogen‐enriched 2, 6‐dicyanopyridine as the precursor. As‐prepared porous carbons possess rich topological defects and ultrahigh specific surface area of up to 3123 m 2 g −1 . As electrocatalysts for CO2 reduction, as‐prepared porous carbons exhibit excellent activity for CO formation with a low onset potential of −283 mV, high CO Faradaic efficiency of up to 99.0% at −0.4 V, which is the state‐of‐the‐art activity among all of reported porous carbons. Density functional theory calculations indicate that pentagonal structure cause the electronegativity of carbon skeletons and act as the main active sites for CO2 reduction. This work not only presents a facile approach for fabricating porous carbons with a high density of topological defects for efficient electrocatalytic CO2 reduction but also provides insights regarding the origin of high activity of topological defects in porous carbons. Abstract : Topological defect‐enriched porous carbons are fabricated through a pyridinic‐N volatilization strategy. The as‐prepared catalysts show the highest catalytic activity toward carbon dioxide reduction among all reported metal‐free catalysts. Pentagonal structure, especially edge pentagon sites are identified as the active sites.